Sonic the hedgehog (2018), volume 6 ebook The last minute. - Flynn, Ian (Sonic the Hedgehog (2018), 2020)
The world has fallen to the Metal Virus, a manufactured plague that transforms all it infects into robotic zombies at Dr. Eggman's command. Even Sonic the Hedgehog has been infected, though his speed has allowed him to keep the virus at bay. Now, Sonic and his friends in the Restoration launch a desperate plan to cure the world! Collects issues #21–24 of the ongoing Sonic The Hedgehog series.